Antifungal Activity of Rice Husk-Derived Liquid Smoke: Growth Suppression of Rhizoctonia solani and Bioactive Compound Profiling - Ankardiansyah Pandu Pradana; Deril Indana Damayanti; Muh Adiwena; Ahmed Ibrahim Alrashid Yousif; Diana Putri (Universitas Sebelas Maret, 2025)
Sheath blight poses a major challenge in rice cultivation, with current control methods relying heavily on synthetic fungicides. Environmentally sustainable alternatives, such as bioactive compounds derived from agricultural waste, offer promising potential for integrated disease management. This study investigated the antifungal efficacy of rice husk-derived liquid smoke against Rhizoctonia solani, the causal agent of rice sheath blight, and identified its active compounds using gas chromatography-mass spectrometry (GC-MS) analysis. Liquid smoke was produced through the pyrolysis of rice husks and incorporated into potato dextrose agar at concentrations of 1%, 2%, 3%, 4%, and 5% (v/v). R. solani was isolated from infected rice plants, and its pathogenicity was confirmed on rice seeds and seedlings. The in vitro antifungal activity was assessed by measuring colony diameter and calculating the percentage of mycelial growth inhibition over 7 days. The results demonstrated that liquid smoke significantly inhibited the growth of R. solani in a concentration-dependent manner (p < 0.001; exact p = 4.36 × 10-²⁴), with the 5% concentration achieving 100% inhibition. Qualitative microscopic observations revealed morphological abnormalities in fungal hyphae at higher concentrations. GC-MS analysis identified 40 bioactive compounds in the liquid smoke, including phenolic compounds and organic acids, which are known for their antimicrobial properties. The findings suggest that rice husk-derived liquid smoke possesses potent antifungal activity against R. solani due to the presence of these compounds. This study concludes that rice husk liquid smoke can serve as an effective, eco-friendly alternative to synthetic fungicides for controlling sheath blight disease in rice cultivation.